Analysis of IT-Assisted PBL-Based Problem Solving Ability at Nurul 'Azizi Integrated Islamic Middle School - Siregar, Muhammad Fadhil Hidayat (PARADIKMA: JURNAL PENDIDIKAN MATEMATIKA, 2024)
Quantitative and quasi-experimental methods were employed in the investigation. Help with IT issues from a technical standpoint Scholars hold freedom and education in high regard. We administered these tests to eighth graders at Nurul Azizi Integrated Islamic Middle School. Thirty pupils make up each of the two VIII B and VIII A Random classes. The study established two groups: one to serve as a control and another to serve as an experimental group. Compare and contrast VIIIA with VIIIB. The control group used more traditional methods, while the experimental group used problem-based learning based on information technology. a research project having a strong emphasis on numerical data and statistical analysis. A statistical analysis was conducted. To estimate or predict something about a broader population, sample statistics can be utilized. Using assumptions about the data's underlying distribution, parametric statistics involves drawing conclusions about population parameters. A hypothesis is tested before any experiments are conducted. 1) The term "normality" describes a state of being typical or adhering to an average or standard. 2) Homogeneity is the attribute of being consistent or having the same makeup or nature throughout. 3) A hypothesis is a theory or prediction that can be investigated by observation or experimentation. The following results came from the study's investigation and discussion: The use of issue-based learning at SMP IT Nurul 'Azizi improves pupils' math problem-solving skills. This result was not unexpected, considering that the control group only managed 70 on average, whereas the experimental group averaged 82.27. Based on a 2-way significant value (t-tailed) of 0.000 and a 5% significance level (5.793>2.002), the problem-based learning strategy used by SMP IT Nurul 'Azizi enhances students' autonomy when compared to traditional methods. Compared to the experimental class, the control group had a lower average score of 74.70 and an average score of 85.83. This research employed a two-way ANOVA with an Î± = 0.05 significance level. Students' ability to learn mathematics independently at SMP IT Nurul 'Azizi was influenced by their learning model (p-value < 0.05) and their baseline mathematical aptitude (high, medium, or poor). This research employed a two-way ANOVA with an Î± = 0.05 significance level. With a significance level of 0.036, the final result is lower than the presumption of significance (0.05).